Attempts to change - Carrillo Mesa, Carolina; Ramos Gomez, Yent; Rodriguez Becerra, Diana Milena (Rastros Rostros, 2002)
The educational method proposed by Dr. Maria Montessori is a broad proposal, which sees the educational process of the child not only as that stage in which the human being begins learning the formal knowledge of mathematics, languages, social sciences, natural sciences, etc., contemplated in the academic standards set by society as valid to prove that one possesses a certain level of knowledge, but also involves in learning the acquisition of individual and group values, the education of the senses and psychomotor development.